Analisis Faktor Pendukung, Tantangan, Dan Strategi Pengembangan Usaha Tempe Irka Di Kota Palu - Fadilla, Nur; Mustika; Aziz, Yuliyana Abd; Taqwa, Moh; Rachmad (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This qualitative descriptive research analyzes the dynamics of Tempe Irka business as an MSME in Palu City through in-depth interviews with informants, highlighting the background of selecting tempe production due to stable demand for traditional high-protein food, supporting factors such as soybean availability, family support, and consumer loyalty, as well as main inhibitors including soybean price fluctuations, weather impacts on fermentation, and market competition. Survival strategies include selecting quality ingredients, consistent production, partnerships with regular buyers, and social media promotion, while development plans encompass product diversification (ready-to-cook/spiced tempe), capacity enhancement, hygienic packaging, and marketing expansion. Framed by SWOT, RBV, MSME management, and business development theories, findings reveal business resilience from internal strengths despite external vulnerabilities, with conclusions emphasizing contributions to the local economy and cultural preservation, accompanied by recommendations for product innovation, digital competitiveness.